2021
DOI: 10.1002/adts.202100293
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking the Computational Costs and Quality of Vibrational Spectra from Ab Initio Simulations

Abstract: The scaling behavior of ab initio molecular dynamics simulations for the different size bulk systems of liquid methanol is presented and thereby the characteristics of every system performing on either a local compute cluster or a supercomputer are analyzed. Additionally, the influence of different parameters on the quality of the infrared and Raman spectra is investigated using different simulation frameworks, including time step, convergence criteria, density functional approximation, and basis set. Both the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 97 publications
1
12
0
Order By: Relevance
“…There are also some differences in the region of C–H stretches, with a shift of computed spectrum to higher energies and increase of its intensity. These results are similar to the findings of a benchmarking study applying different functionals to model the vibrational spectra of liquid methanol . Most functionals (including PBE) underestimate the frequencies below 2000 cm –1 .…”
Section: Resultssupporting
confidence: 86%
“…There are also some differences in the region of C–H stretches, with a shift of computed spectrum to higher energies and increase of its intensity. These results are similar to the findings of a benchmarking study applying different functionals to model the vibrational spectra of liquid methanol . Most functionals (including PBE) underestimate the frequencies below 2000 cm –1 .…”
Section: Resultssupporting
confidence: 86%
“…A modified PB4-D basis is used for deuterium with exponents rescaled according to the mass dependence in the harmonic oscillator model. (Table S1) The basis sets centers are fixed on nuclear (expectation) positions in our calculations, although we note that the centers could have subtle effects on the resulting vibrational spectra. Since electronic exchange–correlation functionals could have a significant influence on the calculated vibrational spectra, we have performed benchmark calculations on functional choice and then adopted the PBE0 functional because DFT-PBE0 gives the most accurate results for molecular vibrational frequencies when compared to CCSD­(T) . (see Table S2 for benchmark details) We do not include electron–nuclei correlations or nuclei–nuclei correlations, and their influence will be left for future studies.…”
Section: Computational Detailsmentioning
confidence: 99%
“…According to our pilot survey for method selection (cf. Supporting Information) and the recent benchmark by Taherivardanjani et al, 30 the variance decreases with the simulation time, system size, and number of mixtures investigated. Hence, there exists a trade-off between calibration coefficient uncertainty and computational effort that has to be found for each application scenario.…”
Section: ■ Results and Discussionmentioning
confidence: 76%
“…For the DFT calculations, we chose the functional BLYP with a double-ζ valence-polarizable basis set (DZVP-MOLOPT-SR-GTH) as implemented in the CP2K software . The recent benchmark by Taherivardanjani et al revealed that double-ζ basis sets yield overall satisfactory results for liquid-phase frequencies of methanol . For BLYP, Irikura et al report (for basis sets of at least 6-31G­(d) size) an accuracy in vibrational frequencies of about 2.5%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation